2011
DOI: 10.1007/s00228-011-1133-1
|View full text |Cite
|
Sign up to set email alerts
|

Epistatic interactions between thiopurine methyltransferase (TPMT) and inosine triphosphate pyrophosphatase (ITPA) variations determine 6-mercaptopurine toxicity in Indian children with acute lymphoblastic leukemia

Abstract: Our results suggest that apart from the individual effect of ITPA 94 C→A, epistatic interactions between the variations of TPMT (*3C, *12) and ITPA (ex2, ex3) are associated with the 6-MP toxicity. Testing these variants facilitates tailoring of the 6-MP therapy in children with ALL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…The difference in the incidence of polymorphic allele from Caucasians is the other explanation for the discrepancies. In addition, there are many other genes which involve the metabolism of mercaptopurine, and synergistic epistatic interaction within these genes was recently reported as an influencing factor for hematological toxicity of mercaptopurine [29]. Dorababu et al reported that epistatic interactions between the variations of TPMT (*3C, *12) and ITPA (rs1127354, rs8362) were associated with the 6-MP toxicity by multifactor dimensionality reduction analysis [29].…”
Section: Discussionmentioning
confidence: 99%
“…The difference in the incidence of polymorphic allele from Caucasians is the other explanation for the discrepancies. In addition, there are many other genes which involve the metabolism of mercaptopurine, and synergistic epistatic interaction within these genes was recently reported as an influencing factor for hematological toxicity of mercaptopurine [29]. Dorababu et al reported that epistatic interactions between the variations of TPMT (*3C, *12) and ITPA (rs1127354, rs8362) were associated with the 6-MP toxicity by multifactor dimensionality reduction analysis [29].…”
Section: Discussionmentioning
confidence: 99%
“…All nine exons of the TPMT gene were amplified on a model 9700 thermal cycler (Applied Biosystems, Foster City, CA, USA) using oligonucleotide primers and conditions as previously described with some modifications 20,21. Direct sequencing was performed using ABI Big Dye Terminator kit v1.1 (Applied Biosystems) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The potential implication of ITPA in the occurrence of ADRs of AZA has been investigated. However, a number of contradictory results have been reported, from an impact of ITPA polymorphism on toxicity to no significant association . This issue remains unresolved, and no obvious statement about the benefit of introducing ITPA assay into clinical practice is currently available .…”
mentioning
confidence: 99%